Pengembangan Media Bergambar Flipbook Pada Pembelajaran Ilmu Pengetahuan Sosial Siswa Kelas IV Sekolah Dasar 101965 Kotasan Tahun Ajaran 2023/2024 - Suriandari, Tri Puja; Syarifah Ainun Harahap (CV.ITTC INDONESIA, 2024)
The aim of this research is to determine the development and feasibility of flipbook learning media. This research is research and development (R&D) using the Borg-Gall method. The data taken from this research are media experts, material experts, teacher responses, and student responses. The results of the research show that the flipbook learning media is suitable for use as a learning media for social studies subjects for class IV students at SDN 101965 Kotasan. This is proven by 98% of the questions being assessed by media experts, 94% by material experts, 93% by teachers, and 94% by students. Based on these results, it can be concluded that the flipbook learning media is suitable for use as a learning media for social studies subjects for class IV students at SDN 101965 Kotasan.